Disinfectant Susceptibility of Bacteria Isolated from Salon Tools in Ishaka Town, Bushenyi District, Uganda - Solange, Gahongayire; Namatovu, Alice; Drago Kato, Charles (IAA Journal of Biological Sciences, 2022)
Bacterial infections are on rising especially resistant strains which cause increase of economic burden to both patients and healthcare providers. Salons shops are recently reported as one of the route for transmitting bacterial pathogens including resistance strains and this was linked to the lack of awareness of salons shop operators on biosafety practices in salons. This study determined prevalence and disinfectant susceptibility patterns of bacteria isolated from salon tools in Ishaka town, Bushenyi District, Uganda. Twenty-five (25) Salon owners/ Head operators were enrolled in this study to determine the level of awareness about the biosafety practice of salons operation using semi-structured questionnaire. Additionally, total of 125 swab samples were collected from different salons tools (combs, brushes, scissors, clippers and shaving machines) and processed using standard Microbiological methods for isolation of bacteria. The isolated bacteria were identified using standard phenotypic methods including analytical profile index (API). Susceptibility patterns of the isolated bacteria to disinfectant were determined using agar well diffusion method. Results obtained from this study showed that a significant number of salon operators (p≤0.05) were aware about the important of disinfectant usage, disinfect tool(s) after use and washing hands /tools after use. Among the 125 swabbed samples collected from the salons, 78 (65.5%) were contaminated with different bacterial species. Clippers were found to have higher (25.6%) contamination among the salon tools from which samples were collected. Of all the tested disinfectants, most resistance was shown with Sodium hypochloride1%. In conclusion, this study showed that, majority of the salon operators were aware about the biosafety practice of salon operation despite the higher contaminations of salons tools.
Keywords: Disinfectant; Susceptibility; Bacteria isolated and Salon tools